(untitled) (Journal of the College of Basic Education, 2022)
It has appeared recently and through modern scientific studies and research, there is great interest in the subject of antioxidants and their extreme importance for athletes and their positive effects with an indication of their negative effect in the event of a decrease in the percentage of its presence in the body, and therefore the interest of the current research was to identify the effect of using some antioxidants (selenium - Omega 3) at the time of the actual training of the runners, not before or after, in order to reduce the percentage of lactic acid concentration and prevent its increase from the normal limit in the blood and muscles during the performance of the runners 400 m race and work on the speed of breaking it down and converting it into glycogen, which helps the runner to produce the energy that enables him to perform the race High speed and stable effect on improving the digital level